Study of the B+ -> J/psi(Lambda)over-barp decay in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2019)
A study of the B+-> J/psi = 8 TeV by the CMS experiment at the LHC, corresponding to an integrated luminosity of 19.6 fb(-1), is presented. The ratio of branching fractions B+-> J/psi B+-> J/psi K is measured to be (1.054 +/- 0.057(stat) +/- 0.035(syst) +/- 0.011 where the last uncertainty reflects the uncertainties in the world-average branching fractions of and K*(892) (+) decays to reconstructed final states. The invariant mass distributions of the J/psi, J/psi systems produced in the B+-> J/psi decay are investigated and found to be inconsistent with the pure phase space hypothesis. The analysis is extended by using a model-independent angular amplitude analysis, which shows that the observed invariant mass distributions are consistent with the contributions from excited kaons decaying to the (Lambda) over barp system.
Keywords: B physics; Hadron-Hadron scattering (experiments)